Role of the construction project team in health and safety management: a study of construction projects in the Wa Municipality of Ghana - Dominic Naaemwan Aasonaa (Occupational Health and Safety Society of Nepal, 2023)
ntroduction: The building industry is vulnerable to a variety of hazards, many of which pose a significant risk to workers' health and safety. This research aimed to examine the role of the construction project team in health and safety management in the Wa Municipality of Ghana. Methods: This study used a descriptive survey with a quantitative approach as the research design. The study's population consisted of 52 construction project sites from the municipal. All 52 construction project sites in the area were chosen for the study. Descriptive and inferential statistics were used to summaries information from respondents. Results: The study revealed that monitoring construction sites and ensuring the companies comply with state regulations on health and safety in the workplace obtained the highest ranking, ensuring workers comply with safety and health procedures and use personal protective equipment at construction project sites were ranked as the topmost roles of the construction project team, poor culture and attitudes existed amongst construction workers, supervisors, and top management of companies toward health and safety. Conclusion: It revealed a lack of health and safety management at all levels of the construction chain. First, there is poor culture and attitudes of construction workers, supervisors, and companies toward health and safety. Secondly, ineffective operation of safety regulation, inefficient institutional frameworks responsible for governing construction activities, and a lack of attention to safety management by main contractors/team. Despite the institutional provisions for construction safety in Ghana (the Labor Act, 2003 and the Factories, Offices, and Shops Act, 1970), there is no compliance with these Acts during construction.